Arrhythmogenic Cardiomyopathy and Skeletal Muscle Dystrophies: Shared Histopathological Features and Pathogenic Mechanisms - Gao, Shanshan; Chen, Suet Nee; Di Nardo, Carlo; Lombardi, Raffaella (Frontiers in Physiology, 2020)
Arrhythmogenic cardiomyopathy (ACM) is a heritable cardiac disease characterized by fibrotic or fibro-fatty myocardial replacement, associated with an increased risk of ventricular arrhythmias and sudden cardiac death. Originally described as a disease of the right ventricle, ACM is currently recognized as a biventricular entity, due to the increasing numbers of reports of predominant left ventricular or biventricular involvement. Research over the last 20 years has significantly advanced our knowledge of the etiology and pathogenesis of ACM. Several etiopathogenetic theories have been proposed; among them, the most attractive one is the dystrophic theory, based on the observation of similar histopathologic features between ACM and skeletal muscle dystrophies (SMDs), such as progressive muscular degeneration, inflammation and tissue replacement by fatty and fibrous tissue. This review will describe the pathophysiological and molecular similarities shared by ACM with SMDs